2003
DOI: 10.1525/sop.2003.46.4.513
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Will and Grace: Mass Audience Reception of a Popular Network Situation Comedy

Abstract: The television situation comedy Will and Grace is notable as the first successful network prime-time series to feature gay characters in a gay milieu. The show's considerable popularity begs the question of how the show's gay sensibility and humor, particularly the gay trickster character, Jack, is received by a heterosexual audience. This article discusses the notion of gay humor, considers the show's history, analyzes several episodes, and scrutinizes the responses of 136 college students who watched the sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 7 publications
0
19
0
1
Order By: Relevance
“…The latter two participants demonstrated a more knowledgeable and critical stance about the television representations of LGB relationships when compared to the reality that they were experiencing through their relationships with real homosexuals. Their opinions overall seemed to match the opinions of scholars that show there are both good and bad elements to 'gay television' (Battles and Hilton-Morrow 2002;Cooper 2003;Hart 2004;Schiappa et al 2006). Despite these positive and negative influences of the media, similar to their experiences as children being exposed to LGB people and issues as a part of their social landscape, mass media sources were another location of "normalizing"…”
Section: Popular Culture Exposurementioning
confidence: 76%
“…The latter two participants demonstrated a more knowledgeable and critical stance about the television representations of LGB relationships when compared to the reality that they were experiencing through their relationships with real homosexuals. Their opinions overall seemed to match the opinions of scholars that show there are both good and bad elements to 'gay television' (Battles and Hilton-Morrow 2002;Cooper 2003;Hart 2004;Schiappa et al 2006). Despite these positive and negative influences of the media, similar to their experiences as children being exposed to LGB people and issues as a part of their social landscape, mass media sources were another location of "normalizing"…”
Section: Popular Culture Exposurementioning
confidence: 76%
“…While the frequency of portrayals of gay men in the media has increased over time, many representations still cling to an outdated stereotype about how a gay man is supposed to act (Cooper, 2003;Fejes & Petrich, 1993;Linneman, 2008;Sarten, 1998). These media images often align with the way that gay men are viewed in society, as numerous studies have confirmed an attribution of feminine characteristics to gay males (Blashill & Powlishta, 2009;Madon, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have established that gay men are frequently presented as feminine in the media (Cooper, 2003;Fejes & Petrich, 1993;Linneman, 2008;Sarten, 1998). Particularly in sitcoms, television representations have tended to rely on stereotypical and comedic portrayals of lesbians as butch and gay men as effeminate (Fejes & Petrich, 1993).…”
mentioning
confidence: 99%
“…And yet, the stereotyped jokes about gays, as told by Jack, the more flamboyant gay man on the television sitcom Will & Grace and the more masculine gay male, Will, illustrate how the same themes used in the 1950s and 1960s can be recycled in our contemporary era. In this case, these are gay jokes, many written by gay men, for a mostly heterosexual audience (see Cooper, 2003).…”
Section: Resultsmentioning
confidence: 99%